Understanding social behaviours across neurodiverse young people: roles of social cognition and self-regulation - Iciar Iturmendi-Sabater; Evdokia Anagnostou; Marc A. Fournier; Jennifer Crosbie; Russell Schachar; Robert Nicolson; Stelios Georgiadis; Elizabeth Kelley; Jessica Jones; Jessica Brian; Hsiang-Yuan Lin; Meng-Chuan Lai (BJPsych Open)
Background Differences in social behaviours are common in young people with neurodevelopmental conditions (NDCs). Recent research challenges the long-standing hypothesis that difficulties in social cognition explain social behaviour differences.